Morphometrical aspects of Ceraeochrysa paraguaria (Navás, 1920) (Neuroptera: Chrysopidae) feeding on different preys - De Bortoli, Sergio Antonio; Murata, Afonso Takao (Federal University of Piauí, 2011)
Ceraeochrysa paraguaria do not has its life history well known, despite its description do not be recent. The present work aimed to evaluate morphometric aspects of C. paraguaria larvae were feeding on Diatraea saccharalis, Sitotroga cerealella e Anagasta kuehniella eggs with the objective to determine the mandibule length, head capsule length, torax + head length, and larvae weight. By the results it was possible to conclude: to the morphometrical parameters, only larvae weight was influenced by the food consumed by the predator, being the nymphal development shorter.